2016
DOI: 10.1016/j.aop.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

A duality web in 2+1 dimensions and condensed matter physics

Abstract: Building on earlier work in the high energy and condensed matter communities, we present a web of dualities in 2 + 1 dimensions that generalize the known particle/vortex duality.Some of the dualities relate theories of fermions to theories of bosons. Others relate different theories of fermions. For example, the long distance behavior of the 2 + 1-dimensional analog of QED with a single Dirac fermion (a theory known as U (1) 1 2 ) is identified with the O(2) Wilson-Fisher fixed point. The gauged version of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
716
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 445 publications
(743 citation statements)
references
References 112 publications
(282 reference statements)
27
716
0
Order By: Relevance
“…These dualities have been the subject of recent attention from a variety of viewpoints. For the special case N = k = N f = 1, these dualities are related to the surface states of time-reversal invariant topological insulators and the fractional quantum Hall effect at half filling [10][11][12][13], lead to a web of dualities [14][15][16][17], and can even be proven on the lattice [18]. They are crucial actors in mapping out the phase diagram of QCD 3 as well as some of its cousins.…”
Section: Jhep01(2018)031mentioning
confidence: 99%
See 2 more Smart Citations
“…These dualities have been the subject of recent attention from a variety of viewpoints. For the special case N = k = N f = 1, these dualities are related to the surface states of time-reversal invariant topological insulators and the fractional quantum Hall effect at half filling [10][11][12][13], lead to a web of dualities [14][15][16][17], and can even be proven on the lattice [18]. They are crucial actors in mapping out the phase diagram of QCD 3 as well as some of its cousins.…”
Section: Jhep01(2018)031mentioning
confidence: 99%
“…In this way the U(k) N − Ns 2 theory becomes 15) which is the right side of the U/U duality (4.4). So the SU/U duality (1.4) implies the U/U duality (4.4) as promised.…”
Section: Jhep01(2018)031mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several authors have suggested that flux attachment also holds for relativistic theories [74][75][76][77][78][79][80]. For example, a map exists between the Dirac fermion and complex scalar theories, both including self-interactions, with the boson coupled to the Chern-Simons field for changing statistics [79,80].…”
Section: Jhep05(2017)135mentioning
confidence: 99%
“…Namely, refs. [33][34][35] argued, based on 3d bosonization dualities [36][37][38][39], that for N f = 1 the SU(2) × U(1) symmetry is in fact enhanced to O(4) (this is related to the self-duality present in this theory [40]). Also, a recent lattice study [41] found no evidence for a symmetry-breaking condensate (for previous lattice studies see refs.…”
Section: Jhep12(2017)054mentioning
confidence: 99%